Prospective analysis of febrile neutropenia patients with bacteraemia: the results of an international ID-IRI study - Erdem, Hakan; Kocoglu, Esra; Ankarali, Handan; El-Sokkary, Rehab; Hakamifard, Atousa; Karaali, Ridvan; Sirmatel, Fatma (Elsevier, 2023)
Objectives: Bacteraemia during the course of neutropenia is often fatal. We aimed to identify factors predicting mortality to have an insight into better clinical management.Methods: The study has a prospective, observational design using pooled data from febrile neutropenia patients with bacteraemia in 41 centres in 16 countries. Polymicrobial bacteraemias were excluded. It was performed through the Infectious Diseases-International Research Initiative platform between 17 March 2021 and June 2021. Univariate analysis followed by a multivariate binary logistic regression model was used to determine independent predictors of 30-d in-hospital mortality (sensitivity, 81.2%; specificity, 65%). Results: A total of 431 patients were enrolled, and 85 (19.7%) died. Haematological malignancies were detected in 361 (83.7%) patients. Escherichia coli (n = 117, 27.1%), Klebsiellae (n = 95, 22% %), Pseudomonadaceae (n = 63, 14.6%), Coagulase-negative Staphylococci (n = 57, 13.2%), Staphylococcus aureus (n = 30, 7%), and Enterococci (n = 21, 4.9%) were the common pathogens. Meropenem and piperacillin-tazobactam susceptibility, among the isolated pathogens, were only 66.1% and 53.6%, respectively. Pulse rate (odds ratio [OR], 1.018; 95% confidence interval [CI], 1.002-1.034), quick SOFA score (OR, 2.857; 95% CI, 2.120- 3.851), inappropriate antimicrobial treatment (OR, 1.774; 95% CI, 1.011-3.851), Gram-negative bacteraemia (OR, 2.894; 95% CI, 1.437-5.825), bacteraemia of non-urinary origin (OR, 11.262; 95% CI, 1.368-92.720), and advancing age (OR, 1.017; 95% CI, 1.001-1.034) were independent predictors of mortality. Bacteraemia in our neutropenic patient population had distinctive characteristics. The severity of infection and the way to control it with appropriate antimicrobials, and local epidemiological data, came forward. Conclusions: Local antibiotic susceptibility profiles should be integrated into therapeutic recommendations, and infection control and prevention measures should be prioritised in this era of rapidly increasing antibiotic resistance.& COPY; 2023 Elsevier Ltd and International Society of Antimicrobial Chemotherapy. All rights reserved.
Keywords: Febrile neutropenia; Bacteraemia; Antimicrobial; Resistance; Antibiotic stewardship